The Effect of Second Language Proficiency on Linguistic Creativity (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2016)
The aim of the study is to investigate the possible effects of second language acquisition on performance in tasks recquiring creativity and linguistic creativity. Participants in the study were Hungarian learners of English (dual-language school pupils and non-language specialized pupils) whose creative ability was measured with a standardized creativity test and tasks compiled for measuring linguistic creativity. Creativity and linguistic creativity were measured by the three aspects of creativity - originality, flexibility and creative fluency. Findings suggest that there is no correlation between results of creativity and linguistic creativity, although daily contact of a second language might have a possitive effect on linguistic creativity.